Insights into genotype-phenotype correlations from CREBBP point mutation screening in a cohort of 46 Rubinstein-Taybi syndrome patients - ELÇİOĞLU, HURİYE NURSEL (WILEY-BLACKWELL, 2015)
The genetic basis of Rubinstein-Taybi syndrome (RSTS), a rare, sporadic, clinically heterogeneous disorder characterized by cognitive impairment and a wide spectrum of multiple congenital anomalies, is primarily due to private mutations in CREBBP (approximately 55% of cases) or EP300 (approximately 8% of cases). Herein, we report the clinical and the genetic data taken from a cohort of 46 RSTS patients, all carriers of CREBBP point mutations. Molecular analysis revealed 45 different gene alterations including 31 inactivating (21 frameshift and 10 nonsense), 10 missense and 4 splicing mutations. Bioinformatic tools and transcript analyses were used to predict the functional effects of missense and splicing alterations. Of the 45 mutations, 42 are unreported and 3 were described previously. Recurrent mutations maybe a key tool in addressing genotype-phenotype correlations in patients sharing the same defects (at the genomic or transcript level) and specific clinical signs, demonstrated here in two cases. The clinical data of our cohort evidenced frequent signs such as arched eyebrows, epicanthus, synophrys and/or frontal hypertrichosis and broad phalanges that, previously overlooked in RSTS diagnosis, now could be considered. Some suggested correlations between organ-specific anomalies and affected CREB-binding protein domains broaden the RSTS clinical spectrum and perhaps will enhance patient follow-up and clinical care.
Keywords: bromo; KIX; HAT-domain; CREBBP; genotype-phenotype correlation; point mutation; Rubinstein-Taybi syndrome; TRANSCRIPTIONAL COACTIVATOR CBP; ACETYLTRANSFERASE ACTIVITY; GENETIC-HETEROGENEITY; HISTONE ACETYLATION; EP300; P300; DELINEATION; DELETIONS; SPECTRUM; HATS